2004
DOI: 10.1021/ac0400212
|View full text |Cite
|
Sign up to set email alerts
|

A Potentiometric and 113Cd NMR Study of Cadmium Complexation by Natural Organic Matter at Two Different Magnetic Field Strengths

Abstract: The binding of cadmium to Suwannee River natural organic matter (NOM) has been investigated across a broad range of Cd/C ratios (0.00056-0.0056) and pH values (3.5-11) by (113)Cd NMR spectroscopy at two magnetic field strengths (B(0) = 9.4 and 11.7 T). Caused by the very peculiar and highly complex nature of the Cd-NOM exchanging system, these (113)Cd NMR spectra are characterized by a pH- and concentration-dependent superposition of slow, intermediate, and fast chemical exchange. The complex interplay of solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 66 publications
0
10
0
1
Order By: Relevance
“…In several studies (e.g., Larive et al, 1996;Li et al, 1998;Otto et al, 2001a,b;Hertkorn et al, 2004;Perdue et al, 2007), 113 Cd NMR spectrometry has been shown to provide far greater insight into the nature of the ligands to which Cd(II) is bound in Cd-DOM complexes and the rates of exchange reactions between the free and various complexed forms of Cd(II). It has been shown clearly that chemical exchange is quite fast at acidic-to-neutral pH and that it becomes much slower at alkaline pH.…”
Section: Dom and Chemical Speciation Of Trace Metal Cationsmentioning
confidence: 99%
“…In several studies (e.g., Larive et al, 1996;Li et al, 1998;Otto et al, 2001a,b;Hertkorn et al, 2004;Perdue et al, 2007), 113 Cd NMR spectrometry has been shown to provide far greater insight into the nature of the ligands to which Cd(II) is bound in Cd-DOM complexes and the rates of exchange reactions between the free and various complexed forms of Cd(II). It has been shown clearly that chemical exchange is quite fast at acidic-to-neutral pH and that it becomes much slower at alkaline pH.…”
Section: Dom and Chemical Speciation Of Trace Metal Cationsmentioning
confidence: 99%
“…The most obvious choices for studies of NOM are DMSO -d 6 or D 2 O (or D 2 O/NaOD, depending on the solubility of the NOM). D 2 O and D 2 O/NaOD have been employed in numerous NOM studies (Buddrus et al, 1989 ;Larive et al, 1996 ;Dixon et al, 1999 ;Fan et al, 2000 ;Simpson et al, 2001c ;Wang et al, 2003 ;Hertkorn et al, 2004 ;Peuravuori, 2005 ) while others utilize DMSO -d 6 (Wais et al, 1996 ;Simpson, 2001 ;Simpson et al, 2003a ;Uyguner et al, 2004 ;Hertkorn et al, 2006 ;. D 2 O and D 2 O/NaOD have advantages in that the solution conformation adopted by the solute are likely to be more predictable than those adopted in DMSO.…”
Section: Sample Preparation For Solution -State Nmrmentioning
confidence: 99%
“…A number of studies of metallic nuclei have examined: aluminum (Howe et al, 1997 ;Lookman et al, 1997 ;Matthias et al, 2003 ), cesium (Xu et al, 2006 ), vanadium (Lu et al, 1998 ), europium , and lithium (Nielsen et al, 2005 ). However, the most widely applied NMR studies of heavy metals have been the study of cadmium (Chung et al, 1996 ;Larive et al, 1996Larive et al, , 1997Li et al, 1998 ;Otto et al, 2001a,b ;Simpson, 2002 ;Hertkorn et al, 2004 ;Grassi and Daquino, 2005 ;Perdue et al, 2005 ). Cadmium NMR studies have been used to quantify 113 Cd binding (Chung et al, 1996 ;Larive et al, 1996 ;Otto et al, 2001b ), evaluate chemical exchange (Larive et al, 1996 ), identify the groups (mainly oxygen, but also nitrogen and sulfur at certain pH values) responsible for binding (Hertkorn et al, 2004 ), and identify specifi c (inner/outer sphere) complexes (Grassi and Daquino, 2005 ).…”
Section: Contaminant Interactionsmentioning
confidence: 99%
See 2 more Smart Citations